THE EFFECT OF HUMAN RESOURCE MANAGEMENT OPTIMIZATION AND COMPETITIVE SYSTEMS ON PRODUCTIVITY ENHANCEMENT THROUGH INNOVATION CAPABILITY AND CREATIVITY AS INTERVENING VARIABLES (A CASE STUDY OF CV. CAPTION MEDIA DIGITAL MALANG) - Suryowanto; Arief Noviarakhman Zagladi; Sopiah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the effect of human resource management (HRM) optimization and competitive systems on productivity enhancement, with innovation capability and creativity as intervening variables at CV. Caption Media Digital Malang. The research employs a quantitative approach with a correlational design, involving approximately 100 employees selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Partial Least Squares (PLS). The results indicate that HRM optimization and competitive systems have a positive and significant effect on productivity. Furthermore, innovation capability and creativity are proven to significantly mediate the relationship between HRM and competitive systems on productivity. The model demonstrates strong explanatory and predictive power, indicating that the integration of effective HRM practices and well-designed competitive systems can enhance organizational productivity through innovation and creativity. This study contributes to the development of HRM and organizational behavior literature, particularly in the digital media industry, by highlighting the importance of innovation and creativity as strategic drivers of productivity.